(untitled) (Andamios, Revista de Investigación Social, 2012)
The notion of female political subject is absent in philosophical thought illustrated. Far from responding to an innocent omission, the articulation of the concepts governing contractualism theorizing in Western political philosophy echo evidence of an exclusion eloquent analysis of the spaces occupied by women in modern societies. Retrieving the conceptual elements of Hobbes, Locke and Rousseau, from feminist literature and critical thinking philosophical elaborate discussion of the space occupied by women in the political subject of modern political philosophy.